Promoting Online Voices for Countering Violent Extremism - Helmus, Todd C. (RAND Corporation, 2013)
American Muslims play an important role in helping counter extremism, and are increasingly using social media to this end. RAND researchers identified challenges facing these Muslim activists, and identified ways to help empower these voices online.